Effects of partially hydrogenated, semi-saturated, and high oleate vegetable oils on inflammatory markers and lipids - Teng, Kim-Tiu; Voon, Phooi-Tee; Cheng, Hwee-Ming; Nesaretnam, K. (2010)
Knowledge about the effects of dietary fats on subclinical inflammation and cardiovascular disease risk are mainly derived from studies conducted in Western populations. Little information is available on South East Asian countries. This current study investigated the chronic effects on serum inflammatory markers, lipids, and lipoproteins of three vegetable oils. Healthy, normolipidemic subjects (n = 41; 33 females, 8 males) completed a randomized, single-blind, crossover study. The subjects consumed high oleic palm olein (HOPO diet: 15% of energy 18:1n-9, 9% of energy 16:0), partially hydrogenated soybean oil (PHSO diet: 7% of energy 18:1n-9, 10% of energy 18:1 trans) and an unhydrogenated palm stearin (PST diet: 11% of energy 18:1n-9, 14% of energy 16:0). Each dietary period lasted 5 weeks with a 7 days washout period. The PHSO diet significantly increased serum concentrations of high sensitivity C-reactive protein compared to HOPO and PST diets (by 26, 23%, respectively; P < 0.05 for both) and significantly decreased interleukin-8 (IL-8) compared to PST diet (by 12%; P < 0.05). In particular PHSO diet, and also PST diet, significantly increased total:HDL cholesterol ratio compared to HOPO diet (by 23, 13%, respectively; P < 0.05), with the PST diet having a lesser effect than the PHSO diet (by 8%; P < 0.05). The use of vegetable oils in their natural state might be preferred over one that undergoes the process of hydrogenation in modulating blood lipids and inflammation.